186k views
1 vote
Which equation is the inverse of y = 9x2 – 4?

2 Answers

4 votes

Answer:-

The two inverses are,


y = \sqrt {(x+4)/(9)}

and,
y =  - \sqrt {(x+4)/(9)}

Step-by-step calculation:-


y = 9 * x^(2) - 4


x^(2) = (y+4)/(9)


x = \mp \sqrt {(y+4)/(9)}

So, the two inverses are,


y = \sqrt {(x+4)/(9)}

and,
y =  - \sqrt {(x+4)/(9)}

User Harry Geo
by
5.7k points
6 votes

Answer:


f^(-1)(x)=\pm (√(x+4) )/(3)

Explanation:

In order to find the inverse of
y=9x^2-4 we need to follow the next steps:

Step 1: Solve for x

Add 4 to both sides:


y+4=9x^2-4+4\\y+4=9x^2

Divide by 9 from both sides:


(y+4)/(9)=(9x^2)/(9)  \\(y+4)/(9)=x^2

Square root from both sides:


√(x^2)=\pm \sqrt{(y+4)/(9)}  \\x=\pm (√(y+4) )/(3)

Step 2: Replace every x with a y and replace every y with an x.


y=\pm (√(x+4) )/(3)

So:


f^(-1)(x)=\pm (√(x+4) )/(3)

Step 3: Verify your work by checking that:


(f \hspace{3}o\hspace{3}f^(-1))(x)=x\\(f^(-1)\hspace{3}o\hspace{3}f)(x)=x


(f \hspace{3}o\hspace{3}f^(-1))(x)=x=9((√(x+4) )/(3))^2 -4=x+4-4=x


(f^(-1)\hspace{3}o\hspace{3}f)(x)=x=(√(9x^2-4+4) )/(3) =(√(9x^2) )/(3) =(3x)/(3) =x

User Takrliu
by
5.5k points